In vivo laser confocal microscopy using the HRT-Rostock cornea module: Diversity and Diagnostic Implications in Patients with Uveitis - Lim, Lyndell L.; Becker, Matthias D.; Mackensen, Friederike (Ocular immunology and inflammation, 2018)
Purpose: Keratic precipitates (KP) are a common feature of uveitis. We prospectively examined KP with the Heidelberg Retinal Tomograph II confocal laser scanning microscope and Rostock Corneal Module (HRT-RCM) to explore their diagnostic implications.Methods: Prospective, observational, multicenter study. HRT-RCM images were classified by two masked observers.Results: 120 scans on 120 eyes from 110 subjects were included. The majority (N = 93) had non-infectious uveitis. Sixty eyes had active disease at scanning. Eight KP morphologies were defined. Agreement between the two masked graders was high (Kappa value across all categories = 0.81). Cluster and nodular KP were associated with active infectious uveitis (p < 0.01): patients with cluster KP (odds ratio [OR] = 3.03, 95% confidence interval [CI]: 1.43, 6.45) and nodular KP (OR = 3.89, 95% CI: 1.42, 10.65) were more likely to have infectious uveitis than those without.Conclusions: Laser confocal microscopy of KP may have a role in determining between infectious and non-infectious uveitis.